The "Enemies of God" in Luther's Final Sermons: Jews, Papists, and the Problem of Blindness to Scripture. Issue 3 (September 2016) - Evener, Vincent
Abstract: Martin Luther's attack on the supposed "enemies of God" in his final sermons was part of the reformer's concerted effort to announce his last will and testament for evangelical Christianity. Chiefly, the article defines what made Jews and "papists" distinct from other enemies in Luther's view. Jews and papists both had possessed Scripture since ancient times; yet they remained unreceptive—for reasons Luther struggled to explain—to the Word therein.